Inovasi E-LKPD Berbasis Etnosains Materi Pembuatan Makanan Ledre Khas Bojonegoro Untuk Peserta Didik Sekolah Dasar - Fitriyaningsih, Fitriyaningsih; Suryanti, Suryanti; Widodo, Wahono (Universitas Negeri Padang, 2025)
This research aims to develop ethnoscience-based E-LKPD products on the material of making typical Bojonegoro ledre for elementary school students. The utilization of local culture through the process of making ledre as ethnoscience-based learning media integrated with digital technology has great potential in supporting the success of the learning process. The research method used is the research and development model of Borg and Gall, which includes: initial data collection through observation and interviews for needs analysis; planning and designing the E-LKPD structure; developing the initial prototype; validation by material and media experts; product revision; small group trials; final revision; and field trials. The validation results showed that the feasibility of E-LKPD obtained an average score from media experts of 96.4% (very credible) and responses from teachers of 98.2% (very credible). Thus, the product is declared feasible to use as learning support at SDN 1 Sobontoro. Ethnoscience-based E-LKPD on the material of making typical Bojonegoro ledre is proven to be valid, practical, and feasible for use in the learning process of students. This study recommends the development of similar media for other grade levels and different local wisdom-based materials.